Effect of Magnetohydrodynamic on Flow of Field of Oldroyd-B Fluid - Nassief, Amaal; Abdulhadi, Ahmad (Iraqi Journal of Science, 2024)
The aim of this paper is to study the effects of magnetohydrodynamic (MHD) onflow of field of Oldroyd-B fluid between two side walls parallel to the plate .The continuity and motion equations, for the problem under consideration areobtained. It is found that the motion equation contains fraction derivative ofdifferent order and the magnetohydrodynamic (MHD) parameter M .The effect of Mupon the velocity field is analyzed ,many types of fractional models are alsoconsidered through taken different values of the fraction derivative order . This hasbeen done through plotting the velocity field by using Mathemitca package .Close form for the stress tensor was obtained in many cases, which have beenstudied before, are covered from our solution.